Ajaran dan Pengaruh semasa Tasawwuf Shaykh Ahmad Al-Sirhindi di Negeri Kedah - Muhammad Khairi bin Mahyuddin; Samsul Bahri bin Andi Galigo; Mohamed Rifai bin Mohamed Ameen; Mohd Rushdan Mohd Jailani (Universiti Sains Islam Malaysia, 2024)
﻿This research studies on the Sufi's thought of Shaykh Ahmad Sirhindi (1564M-1624M), an Indian Sufi scholar in 16 century and his current influential teaching especially in Naqshabandiyyah Mujaddiyyah Ahmadiyyah Order. The practice in the order founded as having a strong impact from Sirhindi's thought which is compiled in his al-Maktubat as a way of purification of soul as well as a way to attain real Gnosis to Allah. The order is traced to be existed in the state of Kedah in the late of the 20 century and it is still accessible until today. An analytical comparison studies had been done toward scholarly writings by Kedah's scholar as well as the practice within Naqshabandiyyah Mujadidiyyah Ahmadiyyah order with al-Maktubat in order to evaluate how far Sirhindi's thought is applicable by the maslzaikh and the disciples of the order in the Kedah. Besides that, in order to know the genuine of Sirhindi's thought and legitimacy of his order whether in line within the majority prominent scholars of Ah1 al-Sunnah wa al- Jamaah or they have deviated from Islamic teaching, so a deep analysis has been made by comparing issues and the practice of the Naqshabandiyyah Mujadidiyyah Ahrnadiyyah with al-Quran, Hadis and other authenticable renowned classical books in Islam. This study hopes would be a great contribution to Muslim community to have correct understanding toward Sufi's role generally and the Naqshabandiyyah order particularly within the spirit of shariat Islarniyyah and the akidah of Ah1 al-Sunnah wa al-Jamaah in Malaysia